Exploring the relationship between dietary patterns and the RS2241766 polymorphism of adiponectin gene in coronary artery disease: a gene-diet interaction study - Rabiathul Bhashira.R; Gopalakrishnan S., Santhini (One Health & Risk Management, 2025)
Introduction. The coronary artery disease remains a major health issue worldwide, especially in low- and middle-income countries where genetic predispositions significantly contribute to its prevalence. Materials and methods. This study, conducted at Chettinad Hospital and Research Institute, Kelambakkam, India, from January to April 2024, investigates the relationship between dietary patterns, genetic variations in Adiponectin, and coronary artery disease risk. Genetic analysis of the adiponectin (45T/G) polymorphism was performed using the Tetra-primer Amplification Refractory Mutation System Polymerase Chain Reaction method. Results. The results revealed notable links between genetic variations, dietary behaviours, and health indicators coronary artery disease patients. Anthropometric and biochemical measurements showed that narrowed coronary arteries were associated with elevated BMI and waist circumference. Lifestyle and sleep patterns also differed significantly between the groups. Among coronary artery disease participants, 64% followed non-vegetarian diets, with higher consumption of red meat and fast food, negatively impacting lipid profiles. The rs2241766 GG genotype of the adiponectin gene was significantly associated with these dietary habits (p<0.01) and obesity (OR=5.1429, p=0.0084). Similarly, the GT genotype demonstrated a strong correlation with obesity (OR=22.15, p < 0.050). Conclusions. This study highlights the intricate connections between genetic predispositions, dietary choices, and coronary artery disease risk. The rs2241766 GG genotype emerged as a strong predictor of coronary artery disease susceptibility compared to the rs2231142 TT genotype, emphasizing the complex interplay of diet, genetics and obesity in coronary artery disease development.